Translating the COVID-19 epidemiological situation into policies and measures: the Belgian experience - De Muylder, Géraldine; Laisnez, Valeska; Stefani, Giulietta; Boulouffe, Caroline; Faes, Christel; Hammami, Naïma; Hubin, Pierre; Molenberghs, Geert; Sans, Jasper; van de Konijnenburg, Cecile; Van der Borght, Stefaan; Brondeel, Ruben; et al. (Frontiers in Public Health, 2024)
The COVID-19 pandemic led to sustained surveillance efforts, which made unprecedented volumes and types of data available. In Belgium, these data were used to conduct a targeted and regular assessment of the epidemiological situation. In addition, management tools were developed, incorporating key indicators and thresholds, to define risk levels and offer guidance to policy makers.Categorizing risk into various levels provided a stable framework to monitor the COVID-19 epidemiological situation and allowed for clear communication to authorities.Although translating risk levels into specific public health measures has remained challenging, this experience was foundational for future evaluation of the situation for respiratory infections in general, which, in Belgium, is now based on a management tool combining different data sources.